Genetic analysis of dormancy and shattering traits in the backcross inbred lines derived from Oryza sativa cv. Swarna / O. nivara Ac. CR100008 - Galimudi, Anusha; KB, Eswari; Gandhudi, Lakshmidevi; LRK, Jai Vidhya; S, Narender Reddy; Addanki, Krishnam Raju; Balakrishnan, Divya; Desiraju, Subrahmanyam; Jukanti, Aravind Kumar; LV, Subba Rao; Badri, Jyothi (ORYZA-An International Journal of Rice, 2020)
Seed dormancy and shattering are important traits influencing the economics of rice farming. The genetic basis of dormancy and shattering traits were investigated in 174 Backcross Inbred Lines (BILs) derived from Oryza sativa cv. Swarna and O. nivara ac. CR100008. Significant variation was observed among the BILs for dormancy and shattering traits. Dormancy of 4-40 days was observed among BILs harvested at 35 days after heading and all the BILs attained > 80% germination by 6th week. Among all the BILs, least dormancy period (4 days) was found in SN-1, 13, 23, 25 and SN-28. Highest dormancy period (40 days) was found in 4 BILs i.e., SN-108, SN-116, SN-117 and SN-122 (40 days). None of the BILs were found to have non-shattering trait, while 2 BILs (SN-38 and SN-163) showed low shattering and 18 BILs were found with very high grain shattering percent. Of the 312 SSRs screened, 94 were polymorphic between the parents. A strategy of combining the DNA pooling from phenotypic extremes and genotyping was employed to detect the putative markers associated with dormancy and shattering traits. Single marker analysis revealed co-segregation of two putative markers RM488 on chromosome 1 and RM247 on chromosome 12 were with dormancy and shattering traits respectively. The putative marker RM488 identified is suitable for the marker assisted transfer of the dormancy shown by O. nivara accession CR100008 for addressing pre harvest sprouting in modern cultivars. Interestingly, O. nivara type allele at RM247 was observed in BILs with low shattering phenotype.